2017
DOI: 10.18632/oncotarget.20015
|View full text |Cite
|
Sign up to set email alerts
|

Probably less than one-tenth of the genes produce only the wild type protein without at least one additional protein isoform in some human cancer cell lines

Abstract: To estimate how many genes produce multiple protein isoforms, we electrophoresed proteins from MCF7 and MDA-MB231 (MB231) human breast cancer cells in SDS-PAGE and excised narrow stripes of the gel at the 48kD, 55kD and 72kD. Proteins in these stripes were identified using liquid chromatography and tandem mass spectrometry. A total of 765, 750 and 679 proteins from MB231 cells, as well as 470, 390 and 490 proteins from MCF7 cells, were identified from the 48kD, 55kD and 72kD stripes, respectively. We arbitrari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…Considering that the prestained protein markers may not be accurate enough and protein migration in SDS-PAGE can be affected by different factors, as described before, 25,26 we arbitrarily allow those proteins with a TMM in the range of 23-29 kD, which is about 10% larger or smaller than 26-kD, to be considered the expected gene products, herein referred to as "the WT," as described before. 25,26 Those proteins with their TMMs above this WT range are categorized into a "smaller-group," while those with their TMMs below this WT range are grouped into a "larger-group," because their positions in the gel were smaller or larger, respectively, than their WT TMMs ( Table 2). Because many genes are expressed as multiple protein isoforms, the categorization is made based on the largest isoform listed in the NCBI database, which may or may not be the canonical WT.…”
Section: Lc-ms/ms Identified a Peptide Unique To The Mouse Cdk4mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the prestained protein markers may not be accurate enough and protein migration in SDS-PAGE can be affected by different factors, as described before, 25,26 we arbitrarily allow those proteins with a TMM in the range of 23-29 kD, which is about 10% larger or smaller than 26-kD, to be considered the expected gene products, herein referred to as "the WT," as described before. 25,26 Those proteins with their TMMs above this WT range are categorized into a "smaller-group," while those with their TMMs below this WT range are grouped into a "larger-group," because their positions in the gel were smaller or larger, respectively, than their WT TMMs ( Table 2). Because many genes are expressed as multiple protein isoforms, the categorization is made based on the largest isoform listed in the NCBI database, which may or may not be the canonical WT.…”
Section: Lc-ms/ms Identified a Peptide Unique To The Mouse Cdk4mentioning
confidence: 99%
“…We have actually mapped the LC-MS/MS-detected peptides onto the largest isoform from 40 genes with the largest TMM among all genes detected and found that only a few of them have the identified peptides evenly distributed throughout the entire sequence (data not shown), similar to what we have reported previously. 25,26 For example, five heat shock proteins (Hspa1a, Hspa8, Hspd1, Hsp90aa1, and Hsp90ab1) have their identified peptides evenly distributed across the entire protein with a high CR. In contrast, for more than 80% of these 40 genes, their proteins have one or more large regions lacking a detected peptide, also similar to what we have reported previously.…”
Section: Many Genes May Express Protein Isoforms Smaller Than the Wmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contained two separate experiments of SDS-PAGE and LC-MS/MS, as described previously [22,23]. In the first experiment [22], human breast cancer cell line MDA-MB231 (MB231) and human embryonic kidney cell line HEK293 were cultured as routine at 37 C in an incubator with 5% CO 2 in 10-cm dishes with a DMEM medium containing 10% bovine fetal serum.…”
Section: Protein Sample Preparation and Sds-pagementioning
confidence: 99%
“…Our studies with this oversimplified top-down approach surprisingly show that most proteins identified are not supposed to appear at a given position of SDS-PAGE because their theoretical molecular masses are either much too large or much too small. Since Western blotting (WB) in most, if not all, cases can detect proteins at the expected position of SDS-PAGE, we concluded that most of those proteins detected unexpectedly at a given SDS-PAGE position might be additional isoforms besides the canonical or the wild type (WT) form [22][23][24]. For instance, ACTB and GAPDH are proteins of about 41.7 kD and 36 kD, respectively, and they can indeed be detected at the corresponding position of SDS-PAGE using WB in probably all published studies.…”
Section: Introductionmentioning
confidence: 99%